Health-related quality of life among farm workers in victor Khanye district, South Africa - Hlophe, Zanele (My University, 2021)
Background Farm workers’ social and economic conditions often have an impact on their health, their ability to live fulfilling lives, and thus their HRQoL. The study sought to investigate and describe HRQoL among farm workers. Methods: A cross-sectional, descriptive, correlational design was used on a sample of 191 (n=191) farm workers from seven farms within the Victor Khanye Municipality in Mpumalanga. The SF-36 Health Survey was used and descriptive and inferential data analysis was done. Results: Female median scores were lower than those of males, which is suggestive of poorer HRQoL in females. There was no statistically significant relationship between any of the eight domains of the SF-36 with education and duration of employment. Existence of a chronic disease was significantly associated with Role Limitations due to physical health, and history of injury was found to be significantly associated with Physical Functioning, Energy/Fatigue and General health. Low median scores in the General Health domain were observed on all the socio demographic features used in this study. Recommendations: A qualitative study to explore the needs of farm workers and expansion of currently provided services and incorporation of occupational health care services into the existing services. Conclusion: Socio-demographic features play a role in HRQoL. Overall, farm workers rated their health as good. However, low mean scores in all socio-demographic aspects in the General Health domain are an indication of perceived poor HRQoL.
A research report submitted in fulfilment of the requirements for the degree Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021